USING ARTIFICIAL INTELLIGENCE IN TEACHING COMPUTER SCIENCE IN HIGHER EDUCATION INSTITUTIONS (Web of Technology: Multidimensional Research Journal, 2024)
The article actualizes the problem of searching for new substantive directions for the development of the content of artificial intelligence training in the modern conditions of digitalization. The authors briefly describe the key technologies based on artificial intelligence proposed by the fourth technological revolution and leading to the digital development of the economy and society. Considering the main philosophical and ethical problems of artificial intelligence, as well as guided by the content of the Code of Ethics of Artificial Intelligence, the article proposes ideas and directions for designing a module for a course on artificial intelligence. The newly developed module, containing questions on the ethical problems of artificial intelligence, will not only aim to form certain competencies on this issue among students, but also to develop the content of artificial intelligence training at different levels of education, taking into account new trends in digitalization.